Simple two-step synthesis of 2,4-disubstituted pyrroles and 3,5-disubstituted pyrrole-2-carbonitriles from enones - Murat Kucukdisli (Beilstein Journal of Organic Chemistry, 2014)
The cyclocondensation of enones with aminoacetonitrile furnishes 3,4-dihydro-2H-pyrrole-2-carbonitriles which can be readily converted to 2,4-disubstituted pyrroles by microwave-induced dehydrocyanation. Alternatively, oxidation of the intermediates produces 3,5-disubstituted pyrrole-2-carbonitriles.